Congenital paroxysmal atrial tachycardia. Issue 8 (August 1976) - Radford, D J; Izukawa, T; Rowe, R D
Abstract : Ten infants who had paroxysmal atrial tachycardia in utero or at birth are reported. Because of apparent fetal distress, caesarean section was performed in 4 cases and labour was induced in 1. Birthweight was generally large for gestational age. Severe ascites and hydrops at birth were manifestations of cardiac failure. Atrial flutter was recorded in 4 infants and supraventricular tachycardia in 5. The WoLff-Parkinson-White syndrome became evident later in 2. Digoxin was given to all 10 infants, and cardioversion was required and was effective in 4. Known recurrences in childhood have occurred in only 1 patient. Congenital atrial tachyarrhythmias may be commoner than generally believed, and fetal electrocardiography may help to avoid unnecessary termination of pregnancy. Blood sugar determinations are important, since neonatal hypoglycaemia was found. Cardioversion should be performed promptly in severely ill infants or if there is no response to digoxin. Care is required to avoid digoxin toxicity.